Pediococcus pentosaceus LI05 alleviates DSS‐induced colitis by modulating immunological profiles, the gut microbiota and short‐chain fatty acid levels in a mouse model. Issue 4 (3rd May 2020) - Bian, Xiaoyuan; Yang, Liya; Wu, Wenrui; Lv, Longxian; Jiang, Xianwan; Wang, Qing; Wu, Jingjing; Li, Yating; Ye, Jianzhong; Fang, Daiqiong; Shi, Ding; Wang, Kaicen; et al.
Summary: The gut microbiota is considered a key factor in pathogenesis and progression of inflammatory bowel disease (IBD). The bacterium Pediococcus pentosaceus LI05 alleviated host inflammation by maintaining the gut epithelial integrity, modulating the host immunity, gut microbiota and metabolism, but its effect on IBD remains unclear. The present study aimed to investigate the role and mechanisms of P. pentosaceus LI05. Mice were administered P. pentosaceus LI05 or phosphate‐buffered saline once daily by oral gavage for 14 days, and colitis was induced by providing mice 2% DSS‐containing drinking water for 7 days. P. pentosaceus LI05 ameliorated colitis in mice and reduced the body weight loss, disease activity index (DAI) scores, colon length shortening, intestinal permeability and the proinflammatory cytokine levels. Furthermore, a significantly altered gut microbiota composition with increased diversity and short‐chain fatty acid (SCFA) production was observed in mice treated with P. pentosaceus LI05. Several genera, including Akkermansia and Faecalibacterium, were differentially enriched in the P. pentosaceus LI05‐treated mice and were negatively correlated with colitis indices and positively correlated with gut barrier markers and SCFA levels. The P. pentosaceus LI05 treatment alleviated intestinal inflammation by maintaining the intestinal epithelial integrity and modulating the immunological profiles, gut microbiome and metabolite composition. Based on our findings, P. pentosaceus LI05 might be applied as potential preparation to ameliorate colitis. Abstract : The P. pentosaceus LI05 treatment alleviated intestinal inflammation by maintaining the intestinal epithelial integrity and modulating the immunological profiles, gut microbiome and metabolite composition. Based on our findings, P. pentosaceus LI05 might be applied as potential preparation to ameliorate colitis.